Bronchoalveolar lavage fluid (BALF) differential leucocyte count in Patients with Chronic Obstructive Pulmonary Diseases (Medical Forum Monthly, 2024)
Objective: The aim of this study is to determine Bronchoalveolar lavage fluid (BALF) differential leukocyte count (DLC) in patients suffering from chronic obstructive pulmonary disease (COPD) and to identify the predominant cell type in our set of population.Study Design: It is a cross sectional study.Place and Duration of Study: This study was conducted at a Tertiary Care Hospital in Karachi, Pakistan from March 2012 till October 2012.Material and Methods: The study comprises of 140 patients with COPD with no treatment or poor compliance to treatment and no history of any interventional procedures. All patients have undergone pulmonary function tests (PFTs) to differentiate obstructive pattern disease from restrictive. Fiber optic bronchoscopy was also done, after which 10 cc of BALF was collected and run for DLC.Results: Patients were divided in two groups A and B according to gender, and each group was further divided in to two subgroups on the basis of age i.e. above 40 years and below 40 years. All patients have higher percentage of lymphocytes as compared to polymorphs.Conclusion: A higher concentration of lymphocytes as compared to polymorphs in COPD patients is considered to be an uncommon in Pakistan as per literature survey is concerned, because very less work is done on BALF analysis. Our study suggests that percentage of lymphocytes in patients suffering from COPD is quite high and cases are not restricted to classical acute pulmonary infections.